Mixed Active and Passive, Heart Rate-Controlled Heat Acclimation Is Effective for Paralympic and Able-Bodied Triathletes - Stephenson, Ben T.; Tolfrey, Keith; Goosey-Tolfrey, Victoria L. (Frontiers in Physiology, 2019)
Purpose To explore the effectiveness of mixed, active and passive heat acclimation (HA), controlling the relative intensity of exercise by heart rate (HR) in paratriathletes (PARA) and determine adaptation differences to able-bodied (AB) triathletes. Methods Seven elite paratriathletes and thirteen AB triathletes undertook an 8-d HA intervention consisting of five HR-controlled sessions and three passive heat exposures (35oC, 63% relative humidity). On the first and last day of HA, heat stress tests were conducted whereby thermoregulatory changes were recorded during at a fixed, submaximal workload. The AB group undertook 20 km cycling time trials pre- and post-HA with performance compared to an AB, non-acclimated control group. Results During the heat stress test, HA lowered core temperature (PARA: 0.27 ± 0.32oC; AB: 0.28 ± 0.34oC), blood lactate concentration (PARA: 0.23 ± 0.15 mmol∙l-1; AB: 0.38 ± 0.31 mmol∙l-1) with concomitant plasma volume expansion (PARA: 12.7 ± 10.6; AB: 6.2 ± 7.7%) (p≤0.047). In the AB group, a lower skin temperature (0.19 ± 0.44oC) and HR (5 ± 6 bpm) with a greater sweat rate (0.17 ± 0.25 l∙h-1) was evident post-HA (p≤0.045) but this was not present for the PARA group (p≥0.177). The AB group improved their performance by an extent greater than the smallest worthwhile change based on the normal variation present with no HA (4.5 vs. 3.7%). Conclusions Paratriathletes are capable of displaying partial HA, albeit not to same extent as AB triathletes. The HA protocol was effective at stimulating thermoregulatory adaptations with performance changes noted in AB triathletes.